2013
DOI: 10.1103/physreva.88.013816
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of detector arrays for measuring intensity correlations of photon pairs

Abstract: Intensity correlation measurements form the basis of many experiments based on spontaneous parametric down-conversion. In the most common situation, two single-photon avalanche diodes and coincidence electronics are used in the detection of the photon pairs, and the coincidence count distributions are measured by making use of some scanning procedure. Here we analyze the measurement of intensity correlations using multielement detector arrays. By considering the detector parameters such as the detection and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Recent works have revealed some features of entanglement between pairs of photons generated by SPDC [20,21], but these techniques have not retrieved the full characteristics the photon pairs, i.e., their full joint probability distribution. Moreover, the theoretical analyses associated with these works were carried out under approximations on the form of the correlation [26][27][28]. In particular, these works assumed a regime of detection in which the two photons never hit the same pixel of the camera, which is counterintuitive when measuring pairs that are strongly correlated in position.…”
mentioning
confidence: 99%
“…Recent works have revealed some features of entanglement between pairs of photons generated by SPDC [20,21], but these techniques have not retrieved the full characteristics the photon pairs, i.e., their full joint probability distribution. Moreover, the theoretical analyses associated with these works were carried out under approximations on the form of the correlation [26][27][28]. In particular, these works assumed a regime of detection in which the two photons never hit the same pixel of the camera, which is counterintuitive when measuring pairs that are strongly correlated in position.…”
mentioning
confidence: 99%
“…The red curve shows Eq. (22) with ⟨ ⟩ = ⟨ ⟩ opt and the known dependence of on threshold, i.e., ( > |0). There is agreement between theory and experiment for all but the highest thresholds, which correspond to the lowest values .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this work is to provide a prescription for optimizing the measurement of the biphoton joint probability distribution. Prior work has examined maximizing the visibility of the genuine biphoton coincidences relative to the accidentals background [22]. There, the authors found an optimum visibility when the count rate from photons is equal to that from electronic noise events but noted that the SNR could be improved by increasing the count rate.…”
Section: Introductionmentioning
confidence: 99%
“…However, our system also allows us to obtain images using very low light levels, as shown in figure 4. The images shown contain between 7300 and 75 000 photons, as counted using the photon counting methodology described in [25]. In this method, a threshold signal is applied to each frame read out from the ICCD camera and any signal over this threshold level is counted as a photon.…”
Section: Resultsmentioning
confidence: 99%